Spatial and seasonal patterns of fine-scale to mesoscale upper ocean dynamics in an Eastern Boundary Current System. (March 2016) - Grados, Daniel; Bertrand, Arnaud; Colas, François; Echevin, Vincent; Chaigneau, Alexis; Gutiérrez, Dimitri; Vargas, Gary; Fablet, Ronan
Highlights: Using acoustic we describe the spatiotemporal patterns of fine-scale ocean dynamic. We point out the existence of intense internal wave and submesoscale activity. Structures less than ∼2 km were more numerous and intense in spring than in summer. Abstract: The physical forcing of the ocean surface includes a variety of energetic processes, ranging from internal wave (IW) to submesoscale and mesoscale, associated with characteristic horizontal scales. While the description of mesoscale ocean dynamics has greatly benefited from the availability of satellite data, observations of finer scale patterns remain scarce. Recent studies showed that the vertical displacements of the oxycline depth, which separates the well-mixed oxygenated surface layer from the less oxygenated deeper ocean, estimated by acoustics, provide a robust proxy of isopycnal displacements over a wide range of horizontal scales. Using a high-resolution and wide-range acoustic data set in the Northern Humboldt Current System (NHCS) off Peru, the spatial and temporal patterns of fine-scale-to-mesoscale upper ocean dynamics are investigated. The spectral content of oxycline/pycnocline profiles presents patterns characteristic of turbulent flows, from the mesoscale to the fine scale, and an energization at the IW scale (2 km–200 m). On the basis of a typology performed on 35, 000 structures we characterized six classes of physical structures according to their shape and scale range. The analysis reveals the existence of distinct features for the fine-scale range below ∼2–3 km, and clearly indicates the existence of intense IW and submesoscale activity over the entire NHCS region. Structures at scales smaller than ∼2 km were more numerous and energetic in spring than in summer. Their spatiotemporal variability supports the interpretation that these processes likely relate to IW generation by interactions between tidal flows, stratification and the continental slope. Given the impact of the physical forcing on the biogeochemical and ecological dynamics in EBUS, these processes should be further considered in future ecosystem studies based on observations and models. The intensification of upper ocean stratification resulting from climate change makes such high-resolution analyses even more critical.